A rationally designed two-dimensional MoSe2/Ti2CO2 heterojunction for photocatalytic overall water splitting: simultaneously suppressing electron–hole recombination and photocorrosion - Cen-Feng Fu; Li, Xingxing; Yang, Jinlong (Chemical science (Cambridge), 2021)
Electron–hole recombination and photocorrosion are two challenges that seriously limit the application of two-dimensional (2D) transition metal dichalcogenides (TMDs) for photocatalytic water splitting. In this work, we propose a 2D van der Waals MoSe2/Ti2CO2 heterojunction that features promising resistance to both electron–hole recombination and photocorrosion existing in TMDs. By means of first-principles calculations, the MoSe2/Ti2CO2 heterojunction is demonstrated to be a direct Z-scheme photocatalyst for overall water splitting with MoSe2 and Ti2CO2 serving as photocatalysts for hydrogen and oxygen evolution reactions, respectively, which is beneficial to electron–hole separation. The ultrafast migration of photo-generated holes from MoSe2 to Ti2CO2 as well as the anti-photocorrosion ability of Ti2CO2 are responsible for photocatalytic stability. This heterojunction is experimentally reachable and exhibits a high solar-to-hydrogen efficiency of 12%. The strategy proposed here paves the way for developing 2D photocatalysts for water splitting with high performance and stability in experiments.